Sosialisasi Manajemen Keuangan di Pondok Pesantren Baitul Qurro Tangerang Selatan - Sutariyono Sutariyono; Adhy Firdaus; Joned C Saksana; Firmansyah Firmansyah; Fahri Fahri; Ika Agustina; Idrisi Raliya Putra; Fisy Amalia; Moh Tahang; Adam Samsudin Noor; Khairul Anam; Moh. Islah (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2021)
This community service aims to improve understanding and financial management skills among the managers of the Baitul Qurro Islamic Boarding School, South Tangerang. This socialization activity was carried out during October 2021. The objects of this activity were Islamic boarding school managers, including the Islamic boarding school head, treasurer and administrative staff. The activity methods used include training, workshops and focus group discussions. The training includes material on financial planning, budget management, bookkeeping and financial reporting. Interactive workshops provide opportunities for participants to apply the theory they have learned through case studies and practical simulations. Focus group discussions are used to identify specific problems faced in financial management in Islamic boarding schools and find joint solutions. The results of this activity showed a significant increase in financial management understanding and skills among participants. They are able to make better financial plans, manage budgets more efficiently, and carry out more transparent and accurate bookkeeping and financial reporting. The implication of this activity is the creation of a better financial management system at the Baitul Qurro Islamic Boarding School, which in turn will support operational sustainability and development of the Islamic boarding school. Apart from that, improving financial management skills is also expected to increase stakeholder accountability and trust in the management of Islamic boarding school funds.